2012
DOI: 10.1111/j.1745-7939.2012.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Home and heterosexuality in Aotearoa New Zealand: The spaces and practices of DIY and home renovation

Abstract: The ways in which domestic spaces function as sites of sexual subjectivity and relationship formation for heterosexual couples is an understudied area in geography. One way to address this gap in knowledge is to focus attention on the varied ways in which heterosexual couples use the practices and spaces of do‐it‐yourself (DIY) and home renovation to construct, materialise and sometimes disrupt their subjectivities and relationships. Taking into consideration the significance of home ownership in New Zealand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These strands result in studies covering topics as diverse as the gendered materiality of home (González, ), translocal homes and home‐making (Hadjiyanni, ), and the connections between family (including non‐human members), home, and its materiality (Bowlby, ; Douglas, ; Power, ; Rose, ). There is also burgeoning work on the interplay between material practices, experience, and domesticity (see e.g., Brown, ; Miller, ), including issues of home as a space of homosexual and heterosexual relationships and its materiality in relation to identity management (Gorman‐Murray, , , ; Morrison, , ).…”
Section: From At‐homeness To Territorialisation: Theoretical Considermentioning
confidence: 99%
“…These strands result in studies covering topics as diverse as the gendered materiality of home (González, ), translocal homes and home‐making (Hadjiyanni, ), and the connections between family (including non‐human members), home, and its materiality (Bowlby, ; Douglas, ; Power, ; Rose, ). There is also burgeoning work on the interplay between material practices, experience, and domesticity (see e.g., Brown, ; Miller, ), including issues of home as a space of homosexual and heterosexual relationships and its materiality in relation to identity management (Gorman‐Murray, , , ; Morrison, , ).…”
Section: From At‐homeness To Territorialisation: Theoretical Considermentioning
confidence: 99%
“…Morrison (2012) comments on how important DIY projects can be to heterosexual 8 subjectivities, with many couples negotiating and building their relationships as they work on their homes together. As couples choose new finishes and designs, their house comes to materially represent their relationship.…”
Section: Home Maintenance and Gendered Identitiesmentioning
confidence: 99%
“…Whilst figures are hard to come by it is suggested that New Zealanders are now more likely to be involved in DIY projects than any other population in the Western world (Mackay et al 2007;Morrison 2012), spending perhaps NZ$1billion at DIY stores each year (Mackay 2011). DIY also figures in New Zealand popular culture, in newspapers, magazines and TV shows (Leonard et al 2004).…”
Section: Researching Home Improvement In New Zealandmentioning
confidence: 99%
“…Taking into consideration as to how kitchens were designed historically, we can then begin to produce a product that allows for the ability to be natural, durable, and reusable. DIY (Do It Yourself) is an act that ties the person to their home by continually materialising identity in the home and is a strong part of New Zealand culture (Morrison, 2012). In New Zealand, it is "common for people to live in a constant state of renovation" that can continue for years, and "more often than not, DIY projects are never completely finished" (Morrison, 2012, p. 124), leading to a crudely finished product.…”
Section: Diy Applicationmentioning
confidence: 99%